(untitled) (Global Journal of Medical Research, 2023)
It should be noted that the development of quality concepts in medical care during the last half of the 20th century has been accompanied by significant changes in the policy and ethics of the health sector and has led to an evolution in terms of the performance of care During the last half of the twentieth century the development of quality concepts in the field of medical care has been accompanied by important changes in the politics and ethics of the health sector and has led to an evolution in terms of health care performance It is obvious that the progress of quality concepts and methods in the field of health care is originally the result of the evolution of quality management in the industrial world